A peculiar new species of the genus Grammacephalus Haupt (Hemiptera: Auchenorrhyncha: Cicadellidae: Deltocephalinae) from Madagascar - Gnezdilov, Vladimir M. (Zootaxa, 2020)
Grammacephalus brevis sp. n. is described from the Makay Massif in the former Toliara Province of Madagascar which is first record of the genus from the island. The species described is peculiar by its short vertex and demonstrates close relationships of Grammacephalus Haupt and Scaphoidophyes Kirkaldy. The characters of Grammacephalus Haupt, Scaphoidophyes Kirkaldy, Capoideus Theron, 1974, Nataretus Theron, 1980, and Platyretus Melichar are discussed.